2019
DOI: 10.1161/jaha.119.013263
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Dysfunction in Patients With Primary Aldosteronism: A Propensity Score–Matching Follow‐Up Study With Tissue Doppler Imaging

Abstract: BackgroundPrimary aldosteronism is the most common cause of secondary hypertension and is associated with left ventricular hypertrophy. However, whether aldosterone excess is responsible for left ventricular (LV) diastolic dysfunction is unknown.Methods and ResultsWe prospectively enrolled 129 patients with aldosterone‐producing adenoma and 120 patients with essential hypertension, and analyzed their clinical, biochemical, and echocardiographic data, including tissue Doppler images. The patients with aldostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 48 publications
1
14
0
1
Order By: Relevance
“…In another study of 24 PA patients who underwent adrenalectomy, diastolic function as assessed by E/A ratio and DT improved, but without statistical significance [62]. In our recent study [93], diastolic function improved after adrenalectomy in the APA patients as evidenced by a significant increase in Em and significant decrease in E/Em ratio. The improvement in diastolic function after adrenalectomy was associated with baseline E/Em and changes in LVMI after adrenalectomy.…”
Section: Treatment Effect On Diastolic Function In Patients With Pa: mentioning
confidence: 76%
See 2 more Smart Citations
“…In another study of 24 PA patients who underwent adrenalectomy, diastolic function as assessed by E/A ratio and DT improved, but without statistical significance [62]. In our recent study [93], diastolic function improved after adrenalectomy in the APA patients as evidenced by a significant increase in Em and significant decrease in E/Em ratio. The improvement in diastolic function after adrenalectomy was associated with baseline E/Em and changes in LVMI after adrenalectomy.…”
Section: Treatment Effect On Diastolic Function In Patients With Pa: mentioning
confidence: 76%
“…However, the severity of diastolic dysfunction is proportional to blood pressure [92]. In our recent study [93], we used propensity score matching analysis to mitigate the effect of blood pressure on diastolic function between aldosterone-producing adenomas (APA) and EH patients. There were 105 patients in each group after matching, and the APA patients had significantly worse diastolic function than the EH patients, as reflected by a lower Em and higher E/Em.…”
Section: Diastolic Function Evaluation In Pa: Tissue Doppler Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the improvement after adrenalectomy was seen in both reversal of left ventricular geometry and also alterations in myocardial texture, as shown by increased cyclic variation of integrated backscatter (CVIBS) and decreased plasma carboxy-terminal propeptide of procollagen type I (PICP) level [88]. We also previously reported that aldosterone-induced left ventricular diastolic dysfunction could be reversed after adrenalectomy [89]. Because of the close relation between left ventricular structure/function and AF genesis, improvement of left ventricular structure/function after PA target treatment may further decrease AF burden.…”
Section: Reversal Of Left Ventricular Mass/echocardiographic Parametersmentioning
confidence: 91%
“…The excess of plasma aldosterone correlated with LVH, early diastolic dysfunction [ 137 , 138 ], and left ventricular enlargement with evidence of subclinical systolic dysfunction [ 139 ], In a prospective study of patients who underwent left heart catheterization due to different cardiac diseases, those with AF and hypertensive cardiomyopathy showed an increased ARR [ 140 ]. The increase in LVH in PA patients was confirmed in a meta-analysis that compared patients with PA and essential hypertension [ 141 ].…”
Section: Comorbiditiesmentioning
confidence: 99%